FCγ Chimeric Receptor-Engineered T Cells: Methodology, Advantages, Limitations, and Clinical Relevance - Caratelli, Sara; Sconocchia, Tommaso; Arriga, Roberto; Coppola, Andrea; Lanzilli, Giulia; Lauro, Davide; Venditti, Adriano; Del Principe, Maria Ilaria; Buccisano, Francesco; Maurillo, Luca; Ferrone, Soldano; Sconocchia, Giuseppe (Frontiers in Immunology, 2017)
For many years disappointing results have been generated by many investigations which have utilized a variety of immunologic strategies to enhance the ability of a patient’s immune system to recognize and eliminate malignant cells. However, in recent years, immunotherapy has been used successfully for the treatment of hematologic and solid malignancies. The impressive clinical responses observed in many types of cancer have convinced even the most skeptical clinical oncologists that a patient’s immune system can recognize and reject his tumor if appropriate strategies are implemented. The success immunotherapy is due to the development of at least three therapeutic strategies. They include tumor-associated antigen (TAA)-specific monoclonal antibodies (mAbs), T cell checkpoint blockade, and TAA-specific chimeric antigen receptors (CARs) T cell-based immunotherapy. However, the full realization of the therapeutic potential of these approaches requires the development of strategies to counteract and overcome some limitations. They include the off-target toxicity and mechanisms of cancer immune evasion which obstacle the successful clinical application of mAbs and CAR T cell-based immunotherapies. Thus, we and others have developed the Fc gamma chimeric receptors (FcCRs)-based strategy. Like CARs, FcCRs are composed of an intracellular tail resulting from the fusion of a co-stimulatory molecule with the T cell receptor  chain. In contrast, the extracellular CAR single chain variable fragment (scFv), which recognizes the targeted TAA, has been replaced with the extracellular portion of the FcRIIIA (CD16). FcCR T cells have a few intriguing features. First, given in combination with mAbs, FcCR T cells mediate anti-cancer activity in vitro and in vivo by an antibody-mediated-cellular-cytotoxicity (ADCC) mechanism. Second, CD16-CR T cells can target multiple cancer types provided that TAA-specific mAbs with the appropriate specificity are available. Third, the off-target effect of CD16-CR T cells may be controlled by withdrawing the mAb administration. The goal of this manuscript was three fold. First, we review the current state-of-the-art of pre-clinical CD16-CR T cell technology. Second, we describe its in vitro and in vivo anti-tumor activity. Lastly, we compare the advantages and limitations of the CD16-CR T cell technology with those of CAR T cell methodology.